In the parenthesis: p^3/5 * p^2/5 = p^5/5 (You just add the exponents for multiplication)
p^5/5 is the same as p^1 or just p.
So now we have p^5 in our numerator and p^5 in our denominator. So that simplifies to 1.
Answer:
f(x) = x² - 9
Step-by-step explanation:
Given x = a is a zero of the polynomial f(x) then (x - a) is a factor
Given zeros are x = 3 and x = - 3, then corresponding factors are
(x - 3) and (x - (- 3) ), that is
(x - 3) and (x + 3)
The function is then the product of the factors, that is
f(x) = (x - 3)(x + 3) ← expand using FOIL
f(x) = x² - 9
Answer:
Jada's book was overdue by 1 more day than Juan's book.
...................
Answer:
40
Step-by-step explanation:
2/8 = 10/40
3/5 = 24/40
Answer:
11, 13 and 15.
Step-by-step explanation:
Let's say that the odd number is "x". If x is for example 15, then the next ODD number would be 15+2=17 and the one after that would be 15+2+2=15+4=19.
Applying that here, we get:
Odd number* the next odd number*the next odd number=2145
x*(x+2)*(x+4)=2145
x*(x^2+4x+2x+8)=2145
x^3+6x^2+8x=2145
By solving the polynomial, you get x=11.
Which makes our three numbers: 11, 13 and 15.
11*13*15=2145. The answer checks.